2020
DOI: 10.48550/arxiv.2002.05854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Edge Crossings of the Greedy Spanner

Abstract: t-spanners are used to approximate the pairwise distances between a set of points in a metric space. They have only a few edges compared to the total number of pairs and they provide a t-approximation on the distance of any two arbitrary points. There are many ways to construct such graphs and one of the most efficient ones, in terms of weight and the number of edges of the resulting graph, is the greedy spanner. In this paper, we study the edge crossings of the greedy spanner for points in the Euclidean plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 50 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…In a recent work, the authors of this paper showed that the number of edge crossings of the greedy spanner in the two dimensional Euclidean plane is linear in the number of vertices [8]. Moreover, they proved that the crossing graph of the greedy spanner has bounded degeneracy, implying the existence of sub-linear separators for these graphs [7].…”
Section: Spanners For Complete Graphsmentioning
confidence: 85%
See 4 more Smart Citations
“…In a recent work, the authors of this paper showed that the number of edge crossings of the greedy spanner in the two dimensional Euclidean plane is linear in the number of vertices [8]. Moreover, they proved that the crossing graph of the greedy spanner has bounded degeneracy, implying the existence of sub-linear separators for these graphs [7].…”
Section: Spanners For Complete Graphsmentioning
confidence: 85%
“…Furthermore, we study the problem in the case of the two dimensional Euclidean plane, where the greedy spanner on a complete weighted graph is known to have constant upper bounds on its lightness [10], maximum degree, and average number of edge intersections per node [8]. We observe that a simple change on the this algorithm can extend these results for unit disk graphs as well.…”
Section: Contributionsmentioning
confidence: 85%
See 3 more Smart Citations